Perilaku Prososial Ditinjau dari Empati dan Kematangan Emosi - Asih, Gusti Yuli; Pratiwi, Margaretha Maria Shinta (Jurnal Psikologi: PITUTUR, 2010)
This recearched was aimed to realize the relation  between  empathy  and  emotional maturity toward prosocial behavior. There were two hypotheses proposed, which, there was a relationship  existed  between  empathy  and emotional maturity. Second hypothesis, there was  a  difference  prosocial  behavior  among man and woman.Indicator  used  for  measuring  prosocial behavior, empathy, and emotional maturity was the use of scale. Subjects used in this research are 49 subjects. Data analysis used regression and  t-test  analysis.  The  result  of  the  test showed  that  there  was  a  significant  positive relationship  between  empathy,  emotional maturity, toward prosocial behavior showed by Rxy=0,932 with p=0,000, and no difference in prosocial behavior among men and women.